Association between echocardiographic parameters of cardiac structure and function and mild cognitive impairment - Kai Zhang; Xiaoxia Liu; Siyu Huang; Xinrui Liu; Meiqi Zhao; Chao Xue; Shijun Xia; Jianzeng Dong; Yu Kong; Changsheng Ma (BMC Cardiovascular Disorders)
Abstract Background Cardiovascular diseases (CVDs) marked with cardiac morphological or hemodynamical abnormalities are associated with mild cognitive impairment (MCI). The links between cardiac structure and function and MCI are not well understood. We aimed to explore the association between echocardiographic parameters of cardiac structure and function and MCI in CVD patients. Methods We conducted an age-, gender-, and education level-matched case–control study in general CVD participants with a 1:3 ratio of MCI (Montreal Cognitive Assessment [MoCA] score < 26 and Mini-Mental State Examination [MMSE] score ≥ 24) and cognitively normal participants at a tertiary hospital in Beijing, China. The echocardiographic cardiac parameters and cognitive status were retrieved through the clinical electronic database from May 2021 to August 2023. Principal component analysis (PCA), negative binomial, and conditional multivariate regression were performed. Results A total of 1136 CVD participants (mean age, 61.2 ± 8.3 years) were included in the study, comprising 289 (25.3%) MCI and 847 cognitively normal participants. Compared to cognitively normal participants, MCI participants had a higher prevalence of left ventricular (LV) diastolic dysfunction (54.0% vs. 40.3%; P < 0.001) and greater interventricular septal thickness (IVST) (1.04 ± 0.20 cm vs. 1.00 ± 0.17 cm; P = 0.002). LV diastolic dysfunction (Beta [SE], 0.234 [0.045]; P < 0.001) and IVST (Beta [SE], 0.034 [0.016]; P = 0.036) were negatively correlated with the MoCA score of global cognitive function. LV diastolic dysfunction (OR, 2.03; 95% CI, 1.48–2.79; P < 0.001) and IVST (OR, 1.14; 95% CI, 1.03–1.27; P = 0.014) were positively associated with MCI, independent of diagnosed CVDs and the conventional MCI risk factors. Conclusions General CVD patients with abnormal echocardiographic LV diastolic dysfunction and IVST were associated with cognitive decline, suggesting further cognitive assessment for MCI. Trial registration Retrospectively registered.